In vitro and in vivo evaluation of antibiotic combination against colistin resistant Acinetobacter baumannii isolated from patients of a tertiary care hospital, Bangladesh - Jahan, Sharmin; Shamsuzzaman, S. M. (International Journal of Research in Medical Sciences, 2024)
Background: Emerging resistance to colistin in clinical Acinetobacter baumannii isolates is of growing concern as these-strain are simultaneously resistant to most antimicrobial agents. Colistin is considered as last resort for treating severe bacterial infections caused by gram negative multidrug resistant bacteria. Since current treatment option for these strains are extremely limited, different antimicrobial combinations were used to see their efficacy against colistin resistant A. baumannii both in vitro and in vivo. Methods: Cross-sectional study was done in the department of Microbiology, Dhaka Medical College, Bangladesh from July, 2017 to June, 2018. Antibiotic susceptibility was performed by disc-diffusion technique and MIC. Colistin resistance genes were detected by PCR. In vitro activity of colistin, tigecycline, imipenem, amikacin and their combinations were evaluated by agar dilution method. Rat septicemic models were made using the colistin resistant A. baumannii and effectiveness of antibiotic combinations were tested in rats. Results: Among 32 isolated A. baumannii 12.5% were colistin resistant. All colistin resistant A. baumannii were positive for lpxA, lpxC, pmrA, pmrB genes; 75% were positive for lpxD gene, 50% were positive for pmrC gene. The proportions of synergy observed in colistin-tigecycline, colistin-imipenem, colistin-amikacin and imipenem-amikacin were 75%, 50%, 50% and 25% respectively in vitro. The best in vivo result appeared in group treated with colistin-tigecycline combination where 100% bacterial clearance from rats was observed while colistin-imipenem combination showed 83.33% clearance. Conclusion: Colistin plus tigecycline or colistin plus imipenem may be alternative treatment option against colistin resistant A. baumannii infection.